Cu(OAc)2-catalyzed hydrazination of cyclopropanols and late-stage transformation to 4, 5-dihydropyrazoles. (19th January 2023) - Zhang, Kui; Wei, Cong; Li, Yan; Yao, Yueyang; Song, Liangliang; Jin, Jia; Cai, Lingchao
Abstract : Promising in vitro antifungal activity was demonstrated by the hydrazine and 4, 5-dihydropyrazole core structures. Abstract : A low-cost and commercially available Cu(OAc)2 catalyzed hydrazination of cyclopropyl alcohols is developed. This procedure featured mild reaction conditions and good to excellent yields, providing a feasible method for the preparation of hydrazine derivatives. One of the hydrazine compounds then underwent a one-pot two-step reaction to yield 4, 5-dihydropyrazoles. Furthermore, encouraging antifungal activity was demonstrated by the hydrazine and 4, 5-dihydropyrazole core structures.